MUI Fatwas and Sharia-Based Policy Governance in Islamic Education Management in Indonesia - Yuspiani, Yuspiani; Muhsin, Muhsin; Mahfudz, Muhsin; Shuhufi, Muhammad; Muhammad, Firdaus (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study examines the influence of Majelis Ulama Indonesia (MUI) fatwas on Islamic education management in Indonesia, particularly in aligning sharia principles with contemporary educational practices. The purpose of this research is to explore the role of MUI fatwas in policy formation, curriculum adjustment, and governance frameworks to address the challenges posed by globalization and digitalization in Islamic education. Using a qualitative approach with a case study method, data were collected through in-depth interviews and document analysis of policies implemented in various Islamic education institutions in Indonesia. The study focused on three key fatwas discussed in Ijtima Ulama forums: the third in 2009, the sixth in 2018, and the seventh in 2021. The findings reveal that MUI fatwas contribute significantly to three areas: the establishment of sharia-compliant educational policies, the adaptation of curricula to contemporary needs, and the promotion of equitable governance in Islamic education institutions. However, challenges such as varying interpretations and resistance from stakeholders hinder effective implementation. This research is original in its comprehensive analysis of the direct and indirect impacts of MUI fatwas on Islamic education management, providing new insights into the intersection of sharia principles and modern educational demands. The study has significant implications for policymakers, educators, and religious scholars. It highlights the need for harmonization between sharia-based fatwas and modern management practices to ensure the sustainability and relevance of Islamic education in Indonesia's evolving sociocultural landscape.